An electrophysiologic study of rabbit ciliary epithelium. - Green, K; Bountra, C; Georgiou, P; House, C (1985)
Microelectrode recordings from cells in rabbit ciliary epithelium have been made in vitro. Ionophoresis of Lucifer Yellow dye from microelectrodes during measurements of potential confirmed that the recordings were intracellular. Dye passed from the impaled cells into adjacent cells in both the nonpigmented and pigmented layers of the epithelium. Electrical coupling between epithelial cells also was observed. The mean (+/- SD) values of the potential measured across the basolateral membranes of the nonpigmented cells was -65 +/- -15 mV (n = 77); the mean value of the input resistance at this intracellular recording site was 37 +/- 28 M omega (n = 17). The membrane potential was reduced by raising the concentration of extracellular potassium but unaffected by changes in the concentrations of sodium, chloride, or bicarbonate ions. After a period of deprivation of extracellular potassium, the cells hyperpolarized without a measurable change in membrane resistance when potassium was restored to the bathing solution; this transient response to potassium was abolished by preincubation with ouabain or by bathing the epithelium in a solution lacking sodium. It was concluded that the ciliary epithelial cells are permeable to potassium but exhibit only a low permeability to sodium, chloride, or bicarbonate ions; that the cells possess an electrogenic Na/K pump; and finally, that all of the cells in the epithelium function as a syncytium.